Catalytic Activity of Cationic and Neutral Silver(I)–XPhos Complexes with Nitrogen Ligands or Tolylsulfonate for Mannich and Aza‐Diels–Alder Coupling Reactions. Issue 1 (24th November 2015) - Grirrane, Abdessamad; Álvarez, Eleuterio; García, Hermenegildo; Corma, Avelino
Abstract: Cationic and neutral silver(I)–L complexes (L=Buchwald‐type biaryl phosphanes) with nitrogen co‐ligands or organosulfonate counter ions have been synthesised and characterised through their structural and spectroscopic properties. At room temperature, both cationic and neutral silver(I)–L complexes are extremely active catalysts in the promotion of the single and double A 3 coupling of terminal (di)alkynes, pyrrolidine and formaldehyde. In addition, the aza‐Diels–Alder two‐ and three‐component coupling reactions of Danishefsky's diene with an imine or amine and aldehyde are efficiently catalysed by these cationic or neutral silver(I)–L complexes. The solvent influences the catalytic performance due to limited complex solubility or solvent decomposition and reactivity. The isolation of new silver(I)–L complexes with reagents as ligands lends support to mechanistic proposals for such catalytic processes. The activity, stability and metal–distal arene interaction of these silver(I)–L catalysts have been compared with those of analogous cationic gold(I) and copper(I) complexes. Abstract : It's Mannich! Cationic and neutral Ag I –XPhos complexes with nitrogen or organosulfonate co‐ligands are extremely active homogenous catalysts, far more active than analogous Cu I and Au I complexes, in the promotion of Mannich and aza‐Diels–Alder coupling reactions. Isolation of some Ag I complexes has shed some light on the reaction mechanisms (see figure).